Overtopping risk evaluation at the portuguese coast: Leixões, Lisbon/Caparica and Sines study cases - Capitão, R. (2017)
To tackle recurrent emergency situations due to adverse sea wave conditions, often observed in Portuguese ports and coasts, a research project (HIDRALERTA) is underway to build a methodology and a system for long-term planning, wave climate forecast and early warning to be applied to those areas. This system deals with phenomena such as run-up, overtopping and flooding. lt wiII eventually empower the nationa! authorities with tools or systems that allow proper identification of risk areas and emergency situations and enable coastal and port authorities to select adequate and timely measures as to avoid Ioss of lives and minimize damages Iikely to arise from emergency situations. This system is now operative and has been already applied to several places along the coast of Portugal.